OBTAINING A WOUND-HEALING EFFECT WHEN USING PHOTON THERAPY IN THE EXPERIMENT - T.M. Kanishyna; L.I. Shkilniak (Український стоматологічний альманах, 2021)
Introduction. The absorption of photon radiation causes biochemical, bioelectrical and bioenergetic effects in the biotissue. These primary effects, which occur directly under the action of photon irradiation, also cause secondary effects. Secondary effects are divided into three groups: analgesic, anti-inflammatory and biostimulating. At the same time, huge resources in the world are spent on the fight against diabetes and its complications. At the heart of the pathogenesis of the most common complications of diabetes are changes in the vessels of the microcirculatory tract that develop during the disease. Therefore, the possibility of using photonic physiotherapeutic effects for the prevention of complications of diabetes is of interest to researchers.